Emotions and bonds in teaching and training Interview with Diana Mazza (Itinerarios Educativos, 2020)
Diana Mazza is a Doctor in College education from Buenos Aires and Graduate in Education Sciences by the University of Buenos Aires. Regular Professor of the Chair of Didactics II of the career of Sciences of Faculty Education of Philosophy and Letters of the University of Buenos Aires. Researcher at Research Institute in Education Sciences from the Faculty of Philosophy and University Letters of Buenos Aires in topics linked to training and to university teaching from a clinical perspective and group. Graduate teacher in various universities national. She was Deputy Director of the UBA XXI Program, of the Secretary of Affairs University academics from Buenos Aires. Consultant from various institutions educational and organizations business in the field of training for the job. Author of various publications in magazines specialized in education and of books, including Homework at the university, edited by Eudeba in 2013